Disciplinary and Criminal Accountability of the Judge in the Kurdistan Region Judicial Authority Law No. 30 of 2007 - Aziz, Sardar Ali (Journal of Legal and Political Studies, 2014)
The penalty and disciplinary interrogation of judges of their acts and attitudes do not comply with their status and their posiand their judicial job. and this interrogation is the interesting point of judicial legislation. So the different legal systems have given them special rules, which determine their disciplinary, civil and criminal responsibility, which are different from the other rules that regulate the rest of state employees. The disciplinary responsibility of judges means; Actions arising from the breach of duty career or more which ends with prove of his/her mistake and disciplinary penalty from the disciplinary authority. Regarding the penalty responsibility; it is unlikely for a judge to commit because of his career or else, comes under the legal concept of a crime ،In order to preserve the prestige and independence of the judiciary authority, the legislature has decided to immunity from prosecution and being arrested before getting the approval of judicial board.
Keywords: Penalty; disciplinary; Judicial legislation; responsibility